1984
DOI: 10.1007/bf00915286
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies to a nuclear/nucleolar antigen in patients with polymyositis overlap syndromes

Abstract: A precipitating antigen-antibody system has been characterized that occurs in patients with polymyositis. At least half of the patients not only have polymyositis but also have scleroderma. The proposed name for this antigen found in calf thymus extract (CTE) is PM-Scl, to indicate the almost universal presence of polymyositis and the frequent occurrence of scleroderma in the patients who make antibodies to this antigen. The antigen is probably nucleolar since all sera which precipitate with the PM-Scl antigen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
69
1
2

Year Published

1985
1985
2001
2001

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(76 citation statements)
references
References 8 publications
4
69
1
2
Order By: Relevance
“…The estimated molecular masses of the proteins found in these studies were 110, 90, 80, 39,37,33,30,27,26,22, and 20 kDa. Comparison of these molecular masses with those of the proteins characterized in the present study suggested that hRrp40, hRrp41 and hRrp46 correspond to the 30-, 27-, and 26-kDa proteins, respectively.…”
Section: Cloning Of Human Homologues Of Yeast Rrp40pmentioning
confidence: 65%
See 1 more Smart Citation
“…The estimated molecular masses of the proteins found in these studies were 110, 90, 80, 39,37,33,30,27,26,22, and 20 kDa. Comparison of these molecular masses with those of the proteins characterized in the present study suggested that hRrp40, hRrp41 and hRrp46 correspond to the 30-, 27-, and 26-kDa proteins, respectively.…”
Section: Cloning Of Human Homologues Of Yeast Rrp40pmentioning
confidence: 65%
“…This complex, initially designated as the polymyositis/scleroderma (PM/Scl) 1 overlap syndrome particle and herein referred to as the human exosome, was reported to contain 11 (25) to 16 (26) subunits ranging from 20 to 110 kDa. Two proteins of this complex were identified as autoantigens, which are targeted by autoantibodies present in the serum of patients suffering from myositis, scleroderma, or PM/Scl overlap syndrome (27). All tested anti-PM/Scl-positive sera recognize a nuclear protein, known as PM/Scl-100, while some also recognize a protein migrating at about 75 kDa (PM/ Scl-75) in SDS-polyacrylamide gel electrophoresis (28 -30).…”
mentioning
confidence: 99%
“…None of the other specificities is primarily associated with DM. Anti-PM-Scl is seen with about equal frequency in PM and DM, although it is particularly associated with myositis-scleroderma overlap (2). Anti-Jo-1 is much more frequently seen in PM than in DM (3).…”
Section: Discussionmentioning
confidence: 99%
“…The followup period was <5 years in 85 patients, [5][6][7][8][9][10] years in 53 patients, and > 10 years in 75 patients. During the period of observation, 99 patients received corticosteroids (mean maximum dosage 33 mg of prednisone equivalent daily), 23 received D-penicillamine, and 16 received cytotoxic drugs (11 took azathioprine, 3 methotrexate, and 2 mizoribine).…”
Section: Methodsmentioning
confidence: 99%